Answer:
the first one
Step-by-step explanation:
if you have a ladder with no steps and it is leaning on a wall it will be facing up if you carry that ladder sideways it will still be parrallel to the opposite poles
if this confuss you I will answer again
You have to divide 4.86 by 18 and that gives you.........
Answer:
A. ![g'(3)=-\frac{1}{2}](https://tex.z-dn.net/?f=g%27%283%29%3D-%5Cfrac%7B1%7D%7B2%7D)
Step-by-step explanation:
We have been given that f be a differentiable function such that
,
,
, and
. The function g is differentiable and
for all x.
We know that when one function is inverse of other function, so:
![g(f(x))=x](https://tex.z-dn.net/?f=g%28f%28x%29%29%3Dx)
Upon taking derivative of both sides of our equation, we will get:
![g'(f(x))*f'(x) =1](https://tex.z-dn.net/?f=g%27%28f%28x%29%29%2Af%27%28x%29%20%3D1)
![g'(f(x))=\frac{1}{f'(x)}](https://tex.z-dn.net/?f=g%27%28f%28x%29%29%3D%5Cfrac%7B1%7D%7Bf%27%28x%29%7D)
Plugging
into our equation, we will get:
![g'(f(6))=\frac{1}{f'(6)}](https://tex.z-dn.net/?f=g%27%28f%286%29%29%3D%5Cfrac%7B1%7D%7Bf%27%286%29%7D)
Since
, then
.
![g'(3)=\frac{1}{f'(6)}](https://tex.z-dn.net/?f=g%27%283%29%3D%5Cfrac%7B1%7D%7Bf%27%286%29%7D)
Since we have been given that
, so we will get:
![g'(3)=\frac{1}{-2}](https://tex.z-dn.net/?f=g%27%283%29%3D%5Cfrac%7B1%7D%7B-2%7D)
![g'(3)=-\frac{1}{2}](https://tex.z-dn.net/?f=g%27%283%29%3D-%5Cfrac%7B1%7D%7B2%7D)
Therefore,
and option A is the correct choice.
1. Plug in the 3 in all the x’s that are in the equation:
(3)2 + y2 = for x2 + y2
(3)2 - y2 = for x2 - y2
This would get you for both equations..
6 + y2 = for x2 + y2
6 - y2 = for x2 - y2
2. Now let’s plug in the value of y which is -4:
6 + (-4)2 = for x2 + y2
6 - (-4)2 = for x2 + y2
This would get you for both equations...
-2 = x2 + y2
14 = x2 - y2
Hope this helped, have an awesome day!